Comparative efficacy of Jaungo, a traditional herbal ointment, and a water-in-oil type non-steroidal moisturizer for radiation-induced dermatitis in patients with breast cancer: a prospective, randomized, single-blind, pilot study - Kim, Eun Hye; Park, Su Bin; Jin, Hayun; Chung, Weon Kuu; Yoon, Seong Woo (Frontiers in Pharmacology, 2023)
Background: Radiation-induced dermatitis (RID) is one of the most prevalent side-effects of conventional cancer therapies; however, there is no standard treatment for its prevention. Therefore, this study aimed to evaluate the comparative efficacy and safety of Jaungo (mainly composed of Lithospermum erythrorhizon Siebold & Zucc. and Angelica sinensis (Oliv.) Diel) and the water-inoil-type non-steroidal moisturizer for the prevention of RID in patients with breast cancer (BC).Methods: This is a prospective, single-blind, pilot randomized controlled trial. Between March 2021 and July 2022, 50 patients were randomly selected to use Jaungo or the moisturizer while undergoing postoperative radiation therapy (RT). Assessments were conducted nine times-every week while the patients underwent RT and 2 weeks after the end of therapy. The primary outcome was the incidence rate of RID grade ≥ 2. The secondary outcomes were the incidence rate of maximum grade RID, time to RID onset, RID-related quality of life (QOL) score, pain intensity, and adverse events.The incidence rate of RID grade ≥ 2 was 24.0% and 20.0% in the Jaungo and the moisturizer groups, respectively, with no significant difference between the groups (P = 0.733). Regarding the secondary outcomes, the incidence rate of maximum grade RID (P = 0.890), mean time to RID onset (P = 0.092), cumulative incidence rate of RID (P = 0.280), RID-related QOL score, and maximum pain intensity (P = 0.844) also did not differ significantly between the groups. None of the subjects in either group experienced severe adverse effects, although one participant in the moisturizer group had mild fever and insomnia.These findings suggest that Jaungo has preventive efficacy without severe side-effects against RID in patients with BC that is comparable to that of the water-in-oil type non-steroidal moisturizer. Further extensive randomized controlled trials with larger sample sizes are warranted to validate our findings.